PENETAPAN DAYA TAMPUNG BEBAN PENCEMARAN SUNGAI BADUNG DI DESA PEMOGAN - Santiari, Made; Nuarsa, I Wayan; Budiarsa Suyasa, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 2 (2016), 2016)
The water quality of Badung River in Pemogan village has exceeded the threshold limits.Therefore, It is needed to determinate the carrying capacity of Badung River. The determination of carrying capacity is very useful to control the disposal of waste into the Badung River. The objective of this study were to determine the sources of pollution, pollutant load and load capacity of Badung river at Pemogan village. Determination of pollutant source done with looked for land use and types of activities along the Badung river Pemogan village followed by field inspections. The pollution load was determined by multiplying the concentration of water quality and flow rate, while the carrying capacity was determined with the help of the program Qual2Kw ver 5.1. Determination of load capacity with Qualk2Kw ver 5.1 has several step such as data collect, the data entry process, calibration, verification and simulation according to the scenario. The result of this study showed sources of pollution that cause a decrease the water quality of Badung river in Pemogan village were non point source (agriculture and settlements) and point source ( flow from upstream ). The pollution load that flow into the Badung river in Pemogan village for BOD, COD and TSS respectively 419,97 kg/ day; 865,66 kg/day dan 160,70 kg/day. Load capacity of Badung river for COD and TSS were 1686.53 kg/day dan 4743.36 kg / day, Meanwhile, the load capacity of Badung River for BOD has overlimits.
Keywords: Badung river; Qual2Kw 5.1; Load capacity; pollutant load.